Avaliação da expressão gênica da telomerase (hTERT) como potencial biomarcador em pacientes pediátricos com leucemia linfoblástica aguda - Nogueira, Beatriz Maria Dias (2022)
Acute Lymphoblastic Leukemia (ALL) is a neoplasm of the hematopoietic system often diagnosed in children and which is characterized by recurrent genetic changes such as aneuploidia and chromosomal rearrangements that usually result in the expression of fused genes or deregulated genes. Many of these changes are associated with a high risk of relapse and treatment failure. In ALL, telomere shortening is one of the potential causes of genomic instability leading to structural and gene rearrangements. Telomerase is the enzyme responsible for maintaining telomere sequences and size and has been identified as a common and important marker in cancer, as data show that it plays a critical role in the proliferation of abnormal cells. The expression of the human telomerase gene (hTERT) in patients with ALL has been studied as a biomarker, and may become a new targeted therapeutic target, since the loss of homeomere-telomerase complex causes dysfunctional telomeres and may cause cellular apoptosis, replicative senescence or, in the worst case, the emergence and development of neoplasms. The aim of this study is to evaluate the gene expression profile of the telomerase enzyme in pediatric patients with ALL from northern Brazil. In the present study we had a total sample of 214 patients in whom they were submitted to analysis of the gene expression of hTERT through the quantitative real-time PCR technique. The results of the study were significant (p<0.001*) in the comparison between controls (N=10) and patients with ALL (N=214), demonstrating a hyperexpression of the enzyme in these patients. Compared to other variables reported in this study, the data were statistically non-significant (p>0.05), presenting an egalitarian expression of the enzyme. We stratified 148 patients from the whole, as they presented complete clinical data in the medical records for statistical analysis and clinical risk stratification. They were stratified into gender, age, immunophenotyping, gene fusion and leukometry, and patients are classified as low risk, medium risk and high risk, in accordance with the criteria established by the World Health Organization (WHO). For comparative statistical analysis, the Chi-Square test was applied based on the correlation between the clinical and epidemiological data of the patients, assuming a significance level of 99% (p≤0.001) and 95% (p≤0.05). The results of the study were significant by the analysis of the Chi-Square test in the comparison between the variables: age and gene fusion (p<0.0001); leukometry and immunophenotyping (p=0.0002) and leukometry and gene fusions (p=0.0002). The p statistically significant value demonstrates the probable influence on the correlation between the variables compared. On the other hand, the comparison between age and immunophenotyping (p=0.3853), the correlation between gender and immunophenotyping (p=0.5586), and, finally, gender and gene fusions (p=0.9998), did not present a significant p value, indicating that the related variables probably do not influence each other. Our results support and point out the need for the implementation of new molecular biomarkers, which allow to direct more precisely the risk in which patients are, and can help in reducing mortality rates for patients with worse prognosis, thus establishing a common biomarker for these patients. By conclusion, the present study demonstrated that the gene expression of the enzyme telomerase occurs abnormally, indicating its hyperexpression. Finally, the analysis of altered gene expression of telomerase may become a possible biomarker as a common indicator among pediatric patients diagnosed with acute lymphoblastic leukemia and, thus, may help in the search for target therapies by verifying factors that may be associated with the prognosis of these patients.